Utilising routine healthcare data and artificial intelligence to support personalised neonatal care and research - Kwok, T'ng Chang (2024)
Introduction Bronchopulmonary dysplasia (BPD) is a unique condition of abnormal lung development in premature infants that leads to long-term respiratory disease. Treatments such as postnatal dexamethasone (PND) can prevent BPD but have significant side effects. A “one size fits all” treatment plan in preterm infants, based on a small number of perinatal characteristics, is no longer justifiable. A more personalised approach is needed to identify the right infants for the right treatment. Artificial intelligence (AI) could support this by analysing patterns within large healthcare datasets providing personalised risk stratification, aiding clinical decision-making and research recruitment.